Design, synthesis and spectroscopic properties of crown ether-capped dibenzotetraaza[14]annulenes - Zwoliński, Krzysztof Miroslaw; Eilmes, Julita (Beilstein Journal of Organic Chemistry, 2019)
The first crown ether-capped dibenzotetraaza[14]annulenes (DBTAAs), featuring two macrocyclic binding sites fixed in a face-to-face orientation, were synthesized in satisfactory 26–28% isolated yields. Direct N-alkylation of 1,4,10-trioxa-7,13-diazacyclopentadecane by symmetric DBTAA derivatives bearing bromoalkoxy pendants proceed smoothly at a reasonable level of dilution (1.25 mM). The structures were fully characterized by HR-ESIMS, FTIR-ATR, 1H and 13C NMR spectroscopy and elemental analysis.
Keywords: crown ether; dibenzotetraaza[14]annulene; DBTAA; macrocycle; Schiff base

Supramolecular Chemistry – Concepts and Perspectives - Lehn, J.-M. (VCH, 1995)

(untitled) - Pedersen, C. J. (J. Am. Chem. Soc., 1967)

Synthetic Multidentate Macrocyclic Compounds - Izatt, R. M.; Christensen, J. K. (Academic Press, Inc., 1978)

(untitled) - Späth, A.; König, B. (Beilstein J. Org. Chem., 2010)

(untitled) - Arduini, A.; Casnati, A.; Pochini, A.; Ungaro, R. (Curr. Opin. Chem. Biol., 1997)

(untitled) - Stadlbauer, S.; Riechers, A.; Späth, A.; König, B. (Chem. – Eur. J., 2008)

(untitled) - Späth, A.; König, B. (Tetrahedron, 2010)

Crown Ethers and Cryptands - Gokel, G. (Royal Society of Chemistry, 1991)

(untitled) - Jiou, J.; Chiravuri, K.; Gudapati, A.; Gassensmith, J. J. (Curr. Org. Chem., 2014)

(untitled) - Kubik, S. (Top. Curr. Chem., 2012)

(untitled) - Rossa, L.; Vögtle, F. (Top. Curr. Chem., 1983)

(untitled) - Collman, J. P.; Zhang, X.; Herrmann, P. C.; Uffelman, E. S.; Boitrel, B.; Straumanis, A.; Brauman, J. I. (J. Am. Chem. Soc., 1994)

(untitled) - Comte, C.; Gros, C. P.; Koeller, S.; Guilard, R.; Nurco, D. J.; Smith, K. M. (New J. Chem., 1998)

(untitled) - Mountford, P. (Chem. Soc. Rev., 1998)

(untitled) - Pawlica, D.; Marszałek, M.; Mynarczuk, G.; Sieroń, L.; Eilmes, J. (New J. Chem., 2004)

(untitled) - Paschke, J.; Kirsch, M.; Korth, H.-G.; de Groot, H.; Sustmann, R. (J. Am. Chem. Soc., 2001)

(untitled) - Sustmann, R.; Korth, H.-G.; Kobus, D.; Baute, J.; Seiffert, K.-H.; Verheggen, E.; Bill, E.; Kirsch, M.; de Groot, H. (Inorg. Chem., 2007)

(untitled) - Bončina, M.; Podlipnik, Č.; Piantanida, I.; Eilmes, J.; Teulade-Fichou, M.-P.; Vesnaver, G.; Lah, J. (Nucleic Acids Res., 2015)

(untitled) - Radić-Stojković, M.; Marjanović, M.; Pawlica, D.; Dudek, Ł.; Eilmes, J.; Kralj, M.; Piantanida, I. (New J. Chem., 2010)

(untitled) - Grolik, J.; Sieroń, L.; Eilmes, J. (Tetrahedron Lett., 2006)

(untitled) - Paquette, J. A.; Gilroy, J. B. (J. Polym. Sci., Part A: Polym. Chem., 2016)

(untitled) - Even, P.; Boitrel, B. (Coord. Chem. Rev., 2006)

(untitled) - Sessler, J. L.; Brucker, E. A. (Tetrahedron Lett., 1995)

(untitled) - Kruse, R.; Breitmaier, E. (Chem. Ber., 1981)

(untitled) - Sakata, K.; Annoura, T. (Inorg. Chim. Acta, 1990)

(untitled) - Sakata, K.; Kawano, T.; Annoura, T. (Synth. React. Inorg. Met.-Org. Chem., 1994)

(untitled) - Sakata, K.; Shimoda, M.; Hashimoto, M. (J. Heterocycl. Chem., 1996)

(untitled) - Hardie, M. J.; Malic, N.; Nichols, P. J.; Raston, C. L. (Tetrahedron Lett., 2001)

(untitled) - Kobuke, Y.; Kokubo, K.; Munakata, M. (J. Am. Chem. Soc., 1995)

(untitled) - Kubik, S.; Goddard, R. (J. Org. Chem., 1999)

(untitled) - Dudek, Ł.; Grolik, J.; Kaźmierska, A.; Szneler, E.; Eilmes, A.; Stadnicka, K.; Eilmes, J. (Tetrahedron Lett., 2011)

(untitled) - Pawlica, D.; Radić-Stojković, M.; Dudek, Ł.; Piantanida, I.; Sieroń, L.; Eilmes, J. (Tetrahedron, 2009)

(untitled) - Geduhn, J.; Walenzyk, T.; König, B. (Curr. Org. Synth., 2007)

(untitled) - Solov'ev, V. P.; Strakhova, N. N.; Kazachenko, V. P.; Solotnov, A. F.; Baulin, V. E.; Raevsky, O. A.; Rüdiger, V.; Eblinger, F.; Schneider, H.-J. (Eur. J. Org. Chem., 1998)

(untitled) - Gatto, V. J.; Arnold, K. A.; Viscariello, A. M.; Miller, S. R.; Morgan, C. R.; Gokel, G. W. (J. Org. Chem., 1986)

(untitled) - Chang, C. K. (J. Am. Chem. Soc., 1977)